STRATEGI PERUSAHAAN MULTINASIONAL DI ERA GLOBALISASI (STUDI KASUS GLOKALISASI DALAM EKSPANSI “INDOMIE” KE PASAR TIMUR TENGAH DAN AFRIKA) - Hartanto Hartanto (Populis : Jurnal Sosial dan Humaniora, 2018)
AbstractGlobalization is characterized by the depletion of the boundaries of economic activities between countries and regions. Economic activities becomes a unified process and involves many countries with different values and cultures. Glocalization appears to respond to this in the presence of a global product with a local context. Indomie as an industrial product is a clear evidence of glocalization in globalization, when something globalize then something should be localized. Globalization and glocalization are like two sides in a single coin.Keywords: Globalization, glocalization, Indomie